Understanding FDACS Pesticide Inspections: PI298, 4/2024 - Bultemeier, Brett; Kraus, Emily; James, Tamara; Richmond, Neil (EDIS, 2024)
Pesticide enforcement in Florida is performed by the Florida Department of Agriculture and Consumer Services (FDACS). As part of their enforcement duties, inspections of facilities, vehicles, and even people using pesticides falls under their authority. These inspections can be random or purpose driven, but all utilize the same forms to guide inspectors. Understanding the content on these forms, and purpose behind the inspections can better prepare those professionals who use pesticides to be compliant with the rules. This publication can be used to perform mock inspections and better understand the inspection process for all.